Die Grundsätze im Sinne der EU-Grundrechtecharta - Schmidt, Johannes; Schmidt, Johannes (Mohr Siebeck, 2010)
Principles in Terms of the Charter of Fundamental Rights of the European Union.
PublicationDate: 20100622
Keywords: Europarecht -- Rechtstheorie -- europäische Grundrechte -- Europäische Grundrechte -- Allgemeines -- Rechtsphilosophie -- Völkerrecht -- Array